"The Greatest Man in Wales": James Ap Gruffydd Ap Hywel and the International Opposition to Henry VIII - Marshall, Peter (The sixteenth century journal, 2008)
This article argues for the historical significance of the career of James ap Gruffydd ap Hywel, a gentleman from south Wales who was the first lay subject of Henry VIII to go into foreign exile as an opponent of the king's break with Rome and repudiation of Queen Catherine. It examines James ap Gruffydd's movements around Wales, Ireland, Scotland, and continental Europe in the 1530s and 1540s as well as his network of supporters and allies at home and overseas. The pattern of official reactions to James ap Gruffydd's intrigues suggests that historians have underestimated both the significance of exile as a conservative resistance strategy in these years and the importance of the British, particularly Welsh, dimension to the evolution of the Henrician Reformation.